2022
DOI: 10.3390/ijerph192215206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Compassion Fatigue and Its Association with Professional Identity in Junior College Nursing Interns: A Cross-Sectional Study

Abstract: Background: The issue of compassion fatigue among clinical nurses has received considerable attention, particularly during the COVID-19 pandemic. Yet, the current status of compassion fatigue among junior college nursing interns remains unclear. Additionally, professional identity can modulate the impact of compassion fatigue or burnout on psychological well-being; however, whether professional identity still works in this group is also unclear. This study aimed to reveal the current status of compassion fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
2
10
0
1
Order By: Relevance
“…During the study period (from November 1st, 2020, to February 28th, 2021), moderate compassion fatigue was observed among intern nursing and midwifery students. This level of emotional stress was consistent with an earlier study conducted among Chinese nursing students [ 6 ] but higher than a study conducted in Chinese junior college intern nursing students from December 2021 to June 2022 [ 45 ]. Therefore, a decline in the degree of compassion fatigue was observed with the declining prevalence of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…During the study period (from November 1st, 2020, to February 28th, 2021), moderate compassion fatigue was observed among intern nursing and midwifery students. This level of emotional stress was consistent with an earlier study conducted among Chinese nursing students [ 6 ] but higher than a study conducted in Chinese junior college intern nursing students from December 2021 to June 2022 [ 45 ]. Therefore, a decline in the degree of compassion fatigue was observed with the declining prevalence of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study show that compassion fatigue is signi cantly negatively correlated with professional identity, which supports H2 and is also consistent with previous research [38] . The study of Yi [17] showed that compassion fatigue of nursing interns not only has a negative impact on happiness, but also reduces their enthusiasm for nursing and professional identity. The formation of professional identity is a continuous development process, and an individual's educational experience, life experience, work experience and social media will all have an impact on their professional identity [17] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the three-dimensional professional identity theory [16] , an individual's recognition of professional value and role value will be enhanced through the development of individual cognition, emotion and intentional behavior, thereby improving individual work engagement. Relevant studies have shown that nurses' compassion fatigue can affect nurses' professional identity [17] , and professional identity plays a crucial role in nurses' work engagement [18] . Therefore, nurses' professional identity may be an important mediating variable in the relationship between compassion fatigue and work engagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that nursing students' professional identity is associated with psychological resilience [16] , empathy fatigue [17] , and death attitudes [18] . A positive perception of the meaning of life can promote nursing students' understanding of the meaning of death and a healthy awareness and positive acceptance of death.…”
Section: Introductionmentioning
confidence: 99%